Verifying the Value of the Conversion Factor from Electrical Conductivity to Total Dissolved Solids Using Gravimetric Method (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Water contains dissolved minerals, commonly referred to as Total Dissolved Solids (TDS), or sometimes as total dissolved salts, whose concentrations vary according to the source and location of the water. TDS (mg/l) can be estimated from electrical conductivity (EC) measurements at 25 °C (mS/cm) by applying a conversion factor (f), which typically ranges between 0.54 and 1.1, as reported in instrument manuals and guidelines. Most EC meters allow switching between different measurement modes, including salinity (g/l), electrical conductivity (µS/cm), and total dissolved solids. (mg/l). This study aims to determine TDS using both gravimetric and conductivity-based methods for a number of laboratory-prepared aqueous solutions with varying concentrations, and to calculate the conversion factor in order to verify its consistency with reported values. For this purpose, aqueous salt mixtures were prepared at concentrations of 100, 1000, and 10000 mg/l, then diluted to specific levels. Their electrical conductivity was measured using an EC meter, while TDS was determined by the gravimetric method. The results showed that the calculated conversion factor agrees with the reference range at low concentrations, but deviates at higher concentrations. Accordingly, the authors recommend applying the gravimetric method to determine TDS at higher concentrations (≥ 500 mg/l), and subsequently calculating the conversion factor to be used for other concentrations